An evaluation of Arabic phonology course among school teachers in a hybrid learning environment - Sahrir, Muhammad Sabri; Zainuddin, Nurkhamimi; Nawi, Amani; Samat, Nur Arifah (2013)
The purpose of this research is to conduct an evaluation of an Arabic Phonology course taken by primary school teachers from different locations in Klang Valley and Selangor. The participants in this research are in service teachers enrolling in a part time degree in the Bachelor of Education (Islamic Studies). The degree programme is specially structured for diploma qualified teachers, aiming at upgrading their academic qualification. The programme is a collaboration between the Ministry of Education, Malaysia and the Institute of Education (INSTED), IIUM and is known as Program Pengsiswazahan Guru (PPG). The learning sessions are conducted during weekends (Saturday and Sunday) in a hybrid learning environment mode (face-to-face and e-learning through the Learning Management System – LMS). The participants selected are from 2 sections out of a total of 6 sections comprising of 57 teachers in academic semester 1, 2012/2013. They were required to respond in a mixed mode survey on the effectiveness of the Arabic Phonology course and the instructors involved. The results show that the course evaluation obtained a mean score of moderate high for evaluation of 3 main criterions with the qualitative feedbacks for course improvement and modifications to suit their diverse level of background in the teaching profession in schools.